Inflation, deflation, and uncertainty: What drives euro area option-implied inflation expectations and are they still anchored in the sovereign debt crisis? - Michael Scharnagl; Jelena Stapf (Deutsche Bundesbank, 2014)
We tackle two questions in this paper: In the sovereign debt crisis, what moves the euro area inflation outlook and has the firm anchoring of medium to long-term inflation expectations been touched? Deriving densities from a new data set on options on the euro area harmonized index of consumer prices provides us with the full distribution of inflation expectations. The daily data set allows us to analyze effects of monetary policy announcements and macro news in a time varying event study framework despite the short sample period from 2009 to 2013. Due to renewed fears of deflation we compare option-implied and statistical density functions to gain insight into deflation risk. Inflation expectations show a decreasing mean but growing uncertainty especially since the intensification of the sovereign debt crisis in mid-2011. Around the same time the influence of monetary policy announcements on inflation expectations diminished. Tail events such as deflation although still contained became more probable. The impact of macroeconomic news to explain inflation probabilities overall decreased and shifted towards countries more affected by the crisis. Concerning the anchoring of inflation expectations the paper provides a twofold result: The mean and low sensitivity to actual news speak for anchored inflation expectations whereas the growing uncertainty reveals market participants concerns about possible extreme inflation or deflation outcomes in the future.
Keywords: C58; E31; E44; G13; 330; Inflation expectations; Deflation; Options; Monetary policy; Financial crisis